Sustainable Development Prinsiples: Legal Aspect Disaster Management Policies - Sulbadana Sulbadana (Fiat Justisia: Jurnal Ilmu Hukum, 2022)
The earthquake, tsunami and liquefaction disaster resulted in casualties, environmental damage, property losses and psychological impacts. According to satellite image data obtained from the International Disaster Charter, the structural damage in Palu City due to the earthquake and tsunami reached 2,403 buildings. This caused the paralysis of Palu City from various aspects with a record of around 70,000 people were displaced. Palu city is one of the Central Sulawesi cities with a very high earthquake potential. Sustainable development is one of the most fundamental principles of international law relating to environmental preservation and development. The concept of sustainable development policy was first introduced in 1987 by the World Commission on Environment and Development (WCED) through its report entitled Our Common Future. In Our Common Future, sustainable development is emphasized as a development which can meet the needs of the present without compromising the ability of future generations to meet their needs. Thus, the concept of sustainable development is essentially fair in utilizing natural resources while still paying attention to the resource needs of future generations. After the disaster in Palu City, the Regional Government attempted to make policies to immediately restore the situation, both physical development in the form of facilities and infrastructure as well as non-physical or social restoration. For this reason, this study aims to determine whether government policies after the earthquake, tsunami and liquefaction are following the principles of Sustainable Development. This research is descriptive-analytical, meaning that this research is not only limited to an activity to collect and compile or explain primary, secondary and tertiary legal materials, but also to analyze them concerning legal theories and the practice of implementing positive law which concerns the problem (research object). The approach used in this legal research is an approach to various international legal instruments related to the object of research as well as to take a historical approach to these international legal instruments, to understand changes and developments in the philosophy that underlies the rule of law to facilitate the analysis of the object of research and the case approach, related to legal issues that will be examined in this study.